2022
DOI: 10.1186/s12955-022-02026-5
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of quality of life questionnaires in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis: a systematic review and meta-analysis

Abstract: Background Patients who suffered from ankylosing spondylitis (AS) or non-radiographic axial spondyloarthritis (nr-axSpA) often have poor quality of life (QoL) and there has been a substantial increase in research on acceptable questionnaires for assessment of QoL. This systematic review aims at examining the validity and reliability of QoL questionnaires in patients with AS/nr-axSpA. Methods Randomized controlled trials (RCTs), cohort trials, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…A cutoff value of 8 was used to identify patients with poor QOL. [27,28] 5. Sleep disturbance: Jenkins Sleep Scale (JSS) is commonly used in epidemiological studies and clinical research that evaluate the severity of sleep disturbance.…”
Section: Disease Activity: (A) the Arabic-validated Version Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…A cutoff value of 8 was used to identify patients with poor QOL. [27,28] 5. Sleep disturbance: Jenkins Sleep Scale (JSS) is commonly used in epidemiological studies and clinical research that evaluate the severity of sleep disturbance.…”
Section: Disease Activity: (A) the Arabic-validated Version Ofmentioning
confidence: 99%
“…Of 103, it was observed that the majority (79.6%) were male. In terms of age distribution, approximately 19.4% fell within the range of 18 to 25 years old, while percentages for other age groups were as follows:[26][27][28][29][30][31][32][33][34][35]-24.3%, [36-45]-35.9%, [46-55]-13.6%, and above 55 years old-6.8%. More than half lived in urban settings, and 43.7% were displaced.…”
mentioning
confidence: 98%
“…Less frequently, AS affects peripheral joints and other extra‐articular organs 6 . Over time, comorbidities, pain, and disabilities lower quality of life and increase costs to the patient and the healthcare system 5,7 …”
Section: Introductionmentioning
confidence: 99%
“…6 Over time, comorbidities, pain, and disabilities lower quality of life and increase costs to the patient and the healthcare system. 5,7 Medical and surgical therapies, rehabilitation and exercise training, and patient education are used for the management of AS. 8 Nonsteroidal anti-inflammatory drugs, anti-rheumatic medications, biologics, and tumor necrosis factor (TNF) inhibitors are commonly recommended medications against AS.…”
Section: Introductionmentioning
confidence: 99%
“…Накоплено достаточно свидетельств того, что при отсутствии адекватного лечения у пациентов с анкилозирующим спондилитом (АС) отмечается низкое КЖ, связанное со здоровьем. В настоящее время КЖ является важным аспектом КИ, изучение которого может внести вклад в улучшение медицинской помощи, прогнозирования активности заболевания, анализа безопасности и определения целей терапии [4].…”
unclassified